2018
DOI: 10.3126/njr.v8i2.22975
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Ultrasound in the Diagnosis of Acute Appendicitis and Correlation with Histopathology

Abstract: Introduction: Acute appendicitis is a common surgical condition; yet its diagnosis can be elusive at times and missed diagnosis can lead to attendant complications of perforation and its sequelae. On the contrary, negative appendectomy subjects one to unnecessary surgery and its physiological and psychological consequences. Among the various available modalities of diagnosis of appendicitis, Ultrasonography(USG) is easily accessible, non invasive, less time consuming, low cost investigation no radiation hazard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…This study revealed that appendicitis mostly occurred at the children's age. It is in line with the results of other studies showing that the incidence of Appendicitis mainly occurred in the children's period ranging from 10 to 18 years old (9).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This study revealed that appendicitis mostly occurred at the children's age. It is in line with the results of other studies showing that the incidence of Appendicitis mainly occurred in the children's period ranging from 10 to 18 years old (9).…”
Section: Discussionsupporting
confidence: 92%
“…Ultrasonography is one of the imaging modalities of the last decade widely used with a variety of considerations that ultrasound is an accessible, mobile, noninvasive, and relatively inexpensive examination. Although it is known that ultrasound has lower sensitivity and specificity values than CT-Scan, this tool is preferred as it has several advantages, as mentioned previously (6)(7)(8)(9). Several studies that have been carried out show the results of ultrasound diagnostic tests as a diagnostic modality for acute appendicitis, which has values that vary from low to high, namely sensitivity and specificity of 60-95%.…”
Section: Introductionmentioning
confidence: 99%
“…HPE study showed AA in 58 out of 64 cases (90.6 %) who were diagnosed with AA on USG. Shreshtha et al found USG to have a sensitivity of 85.7% and specificity of 88.2% in the diagnosis of AA with PPV of 96.4% and NPV of 62.5%( 16 ). Inamdar et al found the accuracy and sensitivity of USG in the diagnosis of AA to be 95% and 95.83% ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although similar visibility rates are reported for acute appendicitis patients, the lower deviation in diameter in ulcerative appendicitis may challenge the feasibility of visualising the appendix. 37 Still, identifying potential characteristics that predict treatment response would enable a patient‐tailored treatment approach for UC patients in the ever‐increasing treatment armamentarium.…”
Section: Discussionmentioning
confidence: 99%